Modified material with high bio-based content and preparation method thereof

By modifying the surface of lignin and mixing it with other polymer materials, bio-based foam modified materials with high bio-based content are prepared, which solves the problem of poor interface compatibility in wood-plastic composite foaming materials and realizes the material Improved degradability and performance.

CN119391036APending Publication Date: 2025-02-07DONGGUAN POLYTECHNIC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411731933.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

Among the existing wood-plastic composite foaming materials, the interface compatibility between the polymer matrix and plant fibers is poor, resulting in poor material performance.

Method used

By modifying the lignin surface, a hydrophobic lignin-GMA-EVA composite material was prepared, and mixed with EVA, POE, TPU and other materials, and a bio-based foamed modified material was prepared by heating extrusion.

Benefits of technology

The interface compatibility between the polymer matrix and plant fibers is improved, and modified materials with high biomass content are prepared, with good mechanical properties and degradability, and can replace non-degradable materials and reduce pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a modified material with high bio-based content and a preparation method thereof. The method comprises the following steps: step 1, weighing raw materials in proportion; step 2, preparing a lignin composite material: modifying the surface of lignin to obtain a lignin hydrophobic material, and then preparing a lignin-GMA-EVA composite material; and step 3, preparing a bio-based composite material: uniformly mixing the lignin-GMA-EVA composite material obtained in the step 2 with EVA, POE, TPU, a foaming agent, a cross-linking agent, zinc oxide, calcium stearate and erucyl amide, and carrying out heating extrusion to prepare the bio-based foaming modified material. The invention also provides the modified material with high bio-based content prepared by the method. The problem that the interfacial compatibility between a polymer matrix and plant fibers is poor is solved, the adopted lignin is a natural biomass material and has good environment friendliness, and the prepared biomass foaming material has the advantages of being renewable and environmentally friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a bio-based composite foaming material in the field of bio-based foaming materials and a preparation method thereof, and in particular, to a modified material with a high bio-based content and a preparation method thereof. Background Art

[0002] There are many traditional foam plastic products on the market now, and the materials used are non-degradable, so there is an urgent need for natural degradable materials to replace non-degradable materials, reduce pollution, and achieve true environmental protection and natural degradation.

[0003] Bio-based foamed polymer composites, as an emerging and rapidly developing material category, have been widely used in interior construction, automotive industry, packaging and other fields. Foamed wood-plastic composites generally perform better than non-foamed wood-plastic composites. Their light weight characteristics not only achieve excellent cost-effectiveness, but also bring excellent specific strength.

[0004] In wood-plastic composite foam materials, plant cellulose is used as a natural material, which is renewable, degradable, low-priced and good quality. However, since the surface of plant fibers contains many polar hydroxyl groups, and most polymers are non-polar or weakly polar, how to solve the problem of poor interfacial compatibility between polymer matrix and plant fibers has always been a hot topic of research. Summary of the invention

[0005] The purpose of the present invention is to provide a bio-based composite foam material and a preparation method, which can solve the problems of the prior art. The obtained modified material with high bio-based content can replace non-degradable materials, reduce pollution, and achieve true environmental protection and natural degradation.

[0006] In order to achieve the above-mentioned purpose, the present invention provides a method for preparing a modified material with a high bio-based content, wherein the method comprises: step 1, weighing each raw material in proportion; step 2, preparing a lignin composite material: modifying the surface of lignin to obtain a lignin hydrophobic material, and then preparing a lignin-GMA-EVA composite material; step 3, preparing a bio-based composite material: mixing the lignin-GMA-EVA composite material obtained in step 2 with EVA, POE, TPU, a foaming agent, a cross-linking agent, zinc oxide, calcium stearate and erucamide, and preparing a bio-based foamed modified material by heating and extruding.

[0007] The preparation method of the modified material with high bio-based content mentioned above, wherein, in the step 2, a titanate coupling agent is first added to the lignin, and the mixture is heated and stirred in a reactor to modify the surface of the lignin into a hydrophobic material, which is then taken out for later use, and then the obtained lignin hydrophobic material is mixed and extruded with EVA-g-GMA through the action of an initiator and a first cross-linking agent to prepare a hydrophobic lignin-GMA-EVA composite material.

[0008] The above-mentioned method for preparing the modified material with high bio-based content, wherein, in the step 2, by mass percentage, the amount of the titanate coupling agent is 0.5%-1.5% of the total mass, the amount of the initiator is 0.02%-0.04% of the total mass, the amount of the first cross-linking agent is 0.01%-0.015% of the total mass, the amount of EVA-g-GMA is 18%-25% of the total mass, and the balance is lignin.

[0009] The above-mentioned method for preparing the modified material with high bio-based content, wherein, in the step 2, the lignin is a powder with a particle size range of 200 mesh to 500 mesh; the initiator is any one of sodium persulfate or potassium persulfate; and the first cross-linking agent is N,N-methylenebisacrylamide.

[0010] The preparation method of the above-mentioned modified material with high bio-based content, wherein, in the step 2, first add a titanate coupling agent to the lignin, then put them into a reactor together, stir for 1 hour at a temperature of 50±5°C, take them out, and then mix the lignin treated with the titanate coupling agent and the initiator, the first cross-linking agent, and EVA-g-GMA in proportion, and add them to a twin-screw extruder, the extruder temperature is set to 80°C-100°C-130°C-140°C-140°C-140°C-140°C-140°C-140°C-140°C-135°C for the die head, the feeding speed is 15rpm, the main engine speed is 145rpm, and the lignin-GMA-EVA composite material is obtained by heating and extrusion.

[0011] The preparation method of the above-mentioned modified material with high bio-based content, wherein, in the step 3, EVA, POE, TPU, lignin-GMA-EVA composite material, foaming agent, second cross-linking agent, zinc oxide, calcium stearate and erucic acid amide are mixed uniformly in proportion and added to a twin-screw extruder, the extruder temperature is set to the die head 80℃-100℃-130℃-140℃-140℃-140℃-140℃-140℃-140℃-140℃-135℃, the feeding speed is 15rpm, the main engine speed is 145rpm, and the bio-based foamed modified material is obtained by heating and extrusion.

[0012] The preparation method of the modified material with high bio-based content mentioned above, wherein, in the step 3, by mass percentage, the amount of lignin-GMA-EVA composite material is 45-50% of the total mass of the mixture; the amount of foaming agent is 3-5% of the total mass of the mixture; the amount of the second cross-linking agent is 0.03-0.05% of the total mass of the mixture; the amount of zinc oxide is 1.5-2% of the total mass of the mixture; the amount of calcium stearate is 0.15-0.3% of the total mass of the mixture; the amount of erucamide is 0.5-0.8% of the total mass of the mixture.

[0013] In the above-mentioned method for preparing the modified material with high bio-based content, in the step 3, the foaming agent is AC foaming agent; and the second cross-linking agent is any one of BIPB and DCP.

[0014] The preparation method of the modified material with high bio-based content mentioned above, wherein, in the step 3, by mass percentage, EVA adopts a material with a VA content of 14-30% and a bio-based content of 40-70%, and the amount of EVA is 25-30% of the total mass of the mixture; POE adopts a material with a melt index of 1g / 10min, and the amount of POE is 5-8% of the total mass of the mixture; TPU adopts a polyester material with a melting point in the range of 100-110°C, and the amount of TPU is 8-10% of the total mass of the mixture.

[0015] The present invention also provides a modified material with high bio-based content prepared by the above method.

[0016] The modified material with high bio-based content and the preparation method thereof provided by the present invention have the following advantages:

[0017] The present invention solves the problem of poor interface compatibility between the polymer matrix and the plant fiber in the existing wood-plastic composite foaming material. The lignin used is a natural biomass material with good environmental protection. The prepared biomass foaming material has the advantages of being renewable and environmentally friendly. Compared with other traditional foaming materials, the bio-based content in the modified material obtained by the present invention is higher, which can replace non-degradable materials, reduce pollution, and achieve true environmental protection and natural degradation.

[0018] The preparation method of the invention is simple and easy to operate, and can prepare a modified material with a high bio-based content that is completely degradable and has excellent mechanical properties. DETAILED DESCRIPTION

[0019] The specific embodiments of the present invention are further described below.

[0020] The method for preparing a modified material with a high bio-based content provided by the present invention comprises: step 1, weighing various raw materials in proportion; step 2, preparing a lignin composite material: modifying the surface of lignin to obtain a lignin hydrophobic material, and then preparing a lignin-GMA-EVA composite material; step 3, preparing a bio-based composite material: uniformly mixing the lignin-GMA-EVA composite material obtained in step 2 with EVA, POE, TPU, a foaming agent, a cross-linking agent, zinc oxide, calcium stearate and erucamide, and preparing the bio-based foamed modified material by heating and extruding.

[0021] Preferably, in step 2, a titanate coupling agent is first added to the lignin, and the mixture is heated and stirred in a reactor to modify the surface of the lignin into a hydrophobic material, which is then taken out for later use, and the obtained lignin hydrophobic material is mixed and extruded with EVA-g-GMA through the action of an initiator and a first cross-linking agent to prepare a hydrophobic lignin-GMA-EVA composite material.

[0022] In step 2, by mass percentage, the amount of titanate coupling agent used is 0.5%-1.5% of the total mass of the lignin composite material, the amount of initiator used is 0.02%-0.04% of the total mass of the lignin composite material, the amount of the first cross-linking agent used is 0.01%-0.015% of the total mass of the lignin composite material, the amount of EVA-g-GMA used is 18%-25% of the total mass of the lignin composite material, and the balance is lignin.

[0023] EVA-g-GMA is obtained by grafting EVA (ethylene vinyl acetate copolymer) with GMA (glycidyl methacrylate) groups and is commercially available.

[0024] In step 2, the lignin is powder with a particle size range of 200-500 mesh; the initiator is any one of sodium persulfate or potassium persulfate; and the first cross-linking agent is N,N-methylenebisacrylamide.

[0025] In step 2, first add a titanate coupling agent to the lignin, then put them into a reactor together, stir them for 1 hour at a temperature of 50±5°C, take them out, and then mix the lignin treated with the titanate coupling agent and the initiator, the first cross-linking agent, and EVA-g-GMA in proportion, and add them to a twin-screw extruder. The extruder temperature is set to 80°C-100°C-130°C-140°C-140°C-140°C-140°C-140°C-140°C-140°C-135°C for the die head, the feeding speed is 15rpm, the main engine speed is 145rpm, and the lignin-GMA-EVA composite material is obtained by heating and extrusion.

[0026] In step 3, EVA, POE, TPU, lignin-GMA-EVA composite material, foaming agent, second cross-linking agent, zinc oxide, calcium stearate and erucic acid amide are mixed uniformly in proportion and added to a twin-screw extruder. The extruder temperature is set to 80°C-100°C-130°C-140°C-140°C-140°C-140°C-140°C-140°C-140°C-135°C for the die head, the feeding speed is 15rpm, the main engine speed is 145rpm, and the bio-based foaming modified material is obtained by heating and extrusion.

[0027] In step 3, by mass percentage, the amount of lignin-GMA-EVA composite material is 45-50% of the total mass of the mixture; the amount of foaming agent is 3-5% of the total mass of the mixture; the amount of the second cross-linking agent is 0.03-0.05% of the total mass of the mixture; the amount of zinc oxide is 1.5-2% of the total mass of the mixture; the amount of calcium stearate is 0.15-0.3% of the total mass of the mixture; and the amount of erucamide is 0.5-0.8% of the total mass of the mixture.

[0028] In step 3, the foaming agent is AC foaming agent (ie, azodicarbonamide); the second cross-linking agent is any one of BIPB (di-tert-butyl peroxide isopropylbenzene) or DCP (diisopropylbenzene peroxide).

[0029] In step 3, by mass percentage, EVA adopts EVA material produced by Braskem with a VA (vinyl acetate) content of 14-30% and a bio-based content of 40-70%, and the amount of EVA is 25-30% of the total mass of the mixture; POE (polyolefin elastomer) adopts POE material with a melt index of 1g / 10min, and the amount of POE is 5-8% of the total mass of the mixture; TPU (thermoplastic polyurethane elastomer) adopts a polyester material with a melting point in the range of 100-110°C, and the amount of TPU is 8-10% of the total mass of the mixture.

[0030] The production equipment and other process conditions used in the present invention are known to those skilled in the art.

[0031] The invention also provides a modified material with high bio-based content prepared by the method.

[0032] The modified material with high bio-based content and the preparation method thereof provided by the present invention are further described below in conjunction with the embodiments.

[0033] Example 1

[0034] A method for preparing a modified material with a high bio-based content, comprising:

[0035] Step 1, weigh each raw material according to proportion.

[0036] Step 2, preparing a lignin composite material: modifying the surface of lignin to obtain a lignin hydrophobic material, and then preparing a lignin-GMA-EVA composite material.

[0037] Preferably, a titanate coupling agent is first added to the lignin, and then the two are put into a reactor together. After heating and stirring at 50° C. for 1 hour, the surface of the lignin is modified into a hydrophobic material, which is then taken out for later use. The obtained lignin hydrophobic material is then mixed and extruded with EVA-g-GMA through the action of an initiator and a first cross-linking agent to prepare a hydrophobic lignin-GMA-EVA composite material.

[0038] More preferably, the lignin treated with a titanate coupling agent and the initiator, the first cross-linking agent, and EVA-g-GMA are mixed in proportion and added to a twin-screw extruder, the extruder temperature is set to a die head of 80°C-100°C-130°C-140°C-140°C-140°C-140°C-140°C-140°C-140°C-135°C, the feed speed is 15rpm, the main engine speed is 145rpm, and the lignin-GMA-EVA composite material is obtained by heating and extruding.

[0039] In terms of mass percentage, the amount of titanate coupling agent is 0.5% of the total mass, the amount of initiator is 0.02% of the total mass, the amount of the first cross-linking agent is 0.01% of the total mass, the amount of EVA-g-GMA is 18% of the total mass, and the balance is lignin.

[0040] The lignin is powder with a particle size range of 200 meshes; the initiator is sodium persulfate; and the first cross-linking agent is N,N-methylenebisacrylamide.

[0041] Step 3, preparing a bio-based composite material: uniformly mixing the lignin-GMA-EVA composite material obtained in step 2 with EVA, POE, TPU, a foaming agent, a cross-linking agent, zinc oxide, calcium stearate and erucamide, and extruding the mixture by heating to prepare a bio-based foaming modified material.

[0042] Preferably, EVA, POE, TPU, lignin-GMA-EVA composite material, foaming agent, second cross-linking agent, zinc oxide, calcium stearate and erucamide are mixed evenly in proportion and added to a twin-screw extruder. The extruder temperature is set to 80°C-100°C-130°C-140°C-140°C-140°C-140°C-140°C-140°C-140°C-135°C for the die head, the feeding speed is 15rpm, the main engine speed is 145rpm, and the bio-based foamed modified material is obtained by heating and extrusion.

[0043] In terms of mass percentage, the amount of lignin-GMA-EVA composite material is 49.85% of the total mass of the mixture; the amount of foaming agent is 5% of the total mass of the mixture; the amount of the second cross-linking agent is 0.05% of the total mass of the mixture; the amount of zinc oxide is 2% of the total mass of the mixture; the amount of calcium stearate is 0.3% of the total mass of the mixture; and the amount of erucamide is 0.8% of the total mass of the mixture.

[0044] The foaming agent is AC foaming agent; the second cross-linking agent is BIPB.

[0045] Calculated by mass percentage, EVA uses materials with a VA content of 30% and a bio-based content of 40%, and the amount of EVA used is 25% of the total mass of the mixture; POE uses materials with a melt index of 1g / 10min, and the amount of POE used is 8% of the total mass of the mixture; TPU uses a polyester material with a melting point in the range of 100-110°C, and the amount of TPU used is 9% of the total mass of the mixture.

[0046] This embodiment also provides a modified material with high bio-based content prepared by the method.

[0047] Example 2

[0048] A method for preparing a modified material with a high bio-based content, comprising:

[0049] Step 1, weigh each raw material according to proportion.

[0050] Step 2, preparing a lignin composite material: modifying the surface of lignin to obtain a lignin hydrophobic material, and then preparing a lignin-GMA-EVA composite material.

[0051] Preferably, a titanate coupling agent is first added to lignin, and then the two are put into a reactor together. After heating and stirring at 55° C. for 1 hour, the surface of the lignin is modified into a hydrophobic material, which is then taken out for later use. The obtained lignin hydrophobic material is then mixed and extruded with EVA-g-GMA through the action of an initiator and a first cross-linking agent to prepare a hydrophobic lignin-GMA-EVA composite material.

[0052] More preferably, the lignin treated with a titanate coupling agent and the initiator, the first cross-linking agent, and EVA-g-GMA are mixed in proportion and added to a twin-screw extruder, the extruder temperature is set to a die head of 80°C-100°C-130°C-140°C-140°C-140°C-140°C-140°C-140°C-140°C-135°C, the feed speed is 15rpm, the main engine speed is 145rpm, and the lignin-GMA-EVA composite material is obtained by heating and extruding.

[0053] In terms of mass percentage, the amount of titanate coupling agent is 1.5% of the total mass, the amount of initiator is 0.04% of the total mass, the amount of the first cross-linking agent is 0.015% of the total mass, the amount of EVA-g-GMA is 25% of the total mass, and the balance is lignin.

[0054] The lignin is powder with a particle size range of 400 meshes; the initiator is potassium persulfate; and the first cross-linking agent is N,N-methylenebisacrylamide.

[0055] Step 3, preparing a bio-based composite material: uniformly mixing the lignin-GMA-EVA composite material obtained in step 2 with EVA, POE, TPU, a foaming agent, a cross-linking agent, zinc oxide, calcium stearate and erucamide, and extruding the mixture by heating to prepare a bio-based foaming modified material.

[0056] Preferably, EVA, POE, TPU, lignin-GMA-EVA composite material, foaming agent, second cross-linking agent, zinc oxide, calcium stearate and erucamide are mixed evenly in proportion and added to a twin-screw extruder. The extruder temperature is set to 80°C-100°C-130°C-140°C-140°C-140°C-140°C-140°C-140°C-140°C-135°C for the die head, the feeding speed is 15rpm, the main engine speed is 145rpm, and the bio-based foamed modified material is obtained by heating and extrusion.

[0057] In terms of mass percentage, the amount of lignin-GMA-EVA composite material is 50% of the total mass of the mixture; the amount of foaming agent is 3% of the total mass of the mixture; the amount of the second cross-linking agent is 0.03% of the total mass of the mixture; the amount of zinc oxide is 1.5% of the total mass of the mixture; the amount of calcium stearate is 0.15% of the total mass of the mixture; and the amount of erucamide is 0.5% of the total mass of the mixture.

[0058] The foaming agent is AC foaming agent; the second cross-linking agent is any one of DCP.

[0059] Calculated by mass percentage, EVA uses materials with a VA content of 14% and a bio-based content of 70%, and the amount of EVA used is 30% of the total mass of the mixture; POE uses materials with a melt index of 1g / 10min, and the amount of POE used is 5% of the total mass of the mixture; TPU uses a polyester material with a melting point in the range of 100-110°C, and the amount of TPU used is 9.82% of the total mass of the mixture.

[0060] This embodiment also provides a modified material with high bio-based content prepared by the method.

[0061] Example 3

[0062] A method for preparing a modified material with a high bio-based content, comprising:

[0063] Step 1, weigh each raw material according to proportion.

[0064] Step 2, preparing a lignin composite material: modifying the surface of lignin to obtain a lignin hydrophobic material, and then preparing a lignin-GMA-EVA composite material.

[0065] Preferably, a titanate coupling agent is first added to the lignin, and then the two are put into a reactor together. After heating and stirring at 45°C for 1 hour, the surface of the lignin is modified into a hydrophobic material, which is then taken out for later use. The obtained lignin hydrophobic material is then mixed and extruded with EVA-g-GMA through the action of an initiator and a first cross-linking agent to prepare a hydrophobic lignin-GMA-EVA composite material.

[0066] More preferably, the lignin treated with a titanate coupling agent and the initiator, the first cross-linking agent, and EVA-g-GMA are mixed in proportion and added to a twin-screw extruder, the extruder temperature is set to a die head of 80°C-100°C-130°C-140°C-140°C-140°C-140°C-140°C-140°C-140°C-135°C, the feed speed is 15rpm, the main engine speed is 145rpm, and the lignin-GMA-EVA composite material is obtained by heating and extruding.

[0067] In terms of mass percentage, the amount of titanate coupling agent is 1% of the total mass, the amount of initiator is 0.03% of the total mass, the amount of the first cross-linking agent is 0.012% of the total mass, the amount of EVA-g-GMA is 20% of the total mass, and the balance is lignin.

[0068] The lignin is powder with a particle size range of 500 meshes; the initiator is sodium persulfate; and the first cross-linking agent is N,N-methylenebisacrylamide.

[0069] Step 3, preparing a bio-based composite material: uniformly mixing the lignin-GMA-EVA composite material obtained in step 2 with EVA, POE, TPU, a foaming agent, a cross-linking agent, zinc oxide, calcium stearate and erucamide, and extruding the mixture by heating to prepare a bio-based foaming modified material.

[0070] Preferably, EVA, POE, TPU, lignin-GMA-EVA composite material, foaming agent, second cross-linking agent, zinc oxide, calcium stearate and erucamide are mixed evenly in proportion and added to a twin-screw extruder. The extruder temperature is set to 80°C-100°C-130°C-140°C-140°C-140°C-140°C-140°C-140°C-140°C-135°C for the die head, the feeding speed is 15rpm, the main engine speed is 145rpm, and the bio-based foamed modified material is obtained by heating and extrusion.

[0071] In terms of mass percentage, the amount of lignin-GMA-EVA composite material is 45% of the total mass of the mixture; the amount of foaming agent is 5% of the total mass of the mixture; the amount of the second cross-linking agent is 0.05% of the total mass of the mixture; the amount of zinc oxide is 2% of the total mass of the mixture; the amount of calcium stearate is 0.3% of the total mass of the mixture; and the amount of erucamide is 0.8% of the total mass of the mixture.

[0072] The foaming agent is AC foaming agent; the second cross-linking agent is DCP.

[0073] Calculated by mass percentage, EVA uses a material with a VA content of 20% and a bio-based content of 50%, and the amount of EVA used is 28.85% of the total mass of the mixture; POE uses a material with a melt index of 1g / 10min, and the amount of POE used is 8% of the total mass of the mixture; TPU uses a polyester material with a melting point in the range of 100-110°C, and the amount of TPU used is 10% of the total mass of the mixture.

[0074] This embodiment also provides a modified material with high bio-based content prepared by the method.

[0075] Example 4

[0076] According to the weight fraction ratio, 80 parts of lignin (200 mesh) were added with 0.5 parts of titanate coupling agent, and stirred in a reactor at 50±5°C for 1 hour; then 0.02 parts of sodium persulfate, 0.01 parts of N,N-methylenebisacrylamide, and 19.47 parts of EVA-g-GMA (model: Japan Sumitomo BF-2B, GMA monomer content: 12%, melt flow rate: MFR=3g / 10min) were added, stirred and mixed evenly, and then released for use.

[0077] The above blended materials were added into the feeding hopper of a twin-screw extruder, and the temperature of the twin-screw extruder was set to: 80°C-100°C-130°C-140°C-140°C-140°C-140°C-140°C-140°C-140°C-135°C (die head), feeding speed of 15 rpm, and main engine speed of 145 rpm to prepare lignin-GMA-EVA composite material.

[0078] By weight, 30 parts of EVA (model Braskem SVT2145R, VA content 14%, bio-based content 40%), 5 parts of POE (model DuPont 8100, MFR = 1.0g / 10min), 8 parts of TPU (model BASF AH-560, softening temperature 85.0-105°C), 49 parts of lignin-GMA-EVA composite material, and 5 parts of AC foaming agent, 0. 0.3 parts of BIPB, 2 parts of zinc oxide, 0.2 parts of calcium stearate and 0.77 parts of erucamide were mixed evenly in proportion and added into a twin-screw extruder. The temperature of the extruder was set to 80℃-100℃-130℃-140℃-140℃-140℃-140℃-140℃-140℃-140℃-135℃ at the die head, the feeding speed was 15rpm, the main engine speed was 145rpm, and the bio-based foaming modified material was obtained by heating and extrusion.

[0079] Example 5

[0080] According to the weight fraction ratio, 80 parts of lignin (200 mesh) were added with 0.5 parts of titanate coupling agent, and stirred in a reactor at 50±5°C for 1 hour; then 0.02 parts of sodium persulfate, 0.01 parts of N,N-methylenebisacrylamide, and 19.47 parts of EVA-g-GMA (Sumitomo BF-2B, GMA monomer content 12%, melt flow rate MFR = 3g / 10min) were added, and the mixture was stirred and mixed evenly, and then released for use.

[0081] The above blended materials were added into the feeding hopper of a twin-screw extruder, and the temperature of the twin-screw extruder was set to: 80°C-100°C-130°C-140°C-140°C-140°C-140°C-140°C-140°C-140°C-135°C (die head), feeding speed of 15 rpm, and main engine speed of 145 rpm to prepare lignin-GMA-EVA composite material.

[0082] By weight, 29 parts of EVA (SVT2180 from Braskem, VA content of 19%, bio-based content of 70%), 8 parts of POE (DuPont 8100, MFR=1.0g / 10min), 8 parts of TPU (AH-560 from BASF, softening temperature of 85.0-105°C), 47 parts of lignin-GMA-EVA composite materials, and 5 parts of AC foaming agent, 0.05 parts of BIPB, 1.85 parts of zinc oxide, 0.3 parts of calcium stearate and 0.8 parts of erucamide are used. After being uniformly mixed in proportion, they are added to a twin-screw extruder. The temperature of the extruder is set to 80°C-100°C-130°C-140°C-140°C-140°C-140°C-140°C-140°C-140°C-135°C at the die head, the feeding speed is 15rpm, the main engine speed is 145rpm, and the bio-based foamed modified material is obtained by heating and extrusion.

[0083] Example 6

[0084] According to the weight fraction ratio, 75 parts of lignin (500 mesh) were added with 1.5 parts of titanate coupling agent, and stirred in a reactor at 50±5°C for 1 hour; then 0.04 parts of potassium persulfate, 0.015 parts of N,N-methylenebisacrylamide, and 23.445 parts of EVA-g-GMA (Sumitomo BF-2B, GMA monomer content 12%, melt flow rate MFR = 3g / 10min) were added, and the mixture was stirred and mixed evenly, and then released for use.

[0085] The above blended materials were added into the feeding hopper of a twin-screw extruder, and the temperature of the twin-screw extruder was set to: 80°C-100°C-130°C-140°C-140°C-140°C-140°C-140°C-140°C-140°C-135°C (die head), feeding speed of 15 rpm, and main engine speed of 145 rpm to prepare lignin-GMA-EVA composite material.

[0086] By weight, 28 parts of EVA (SVT2145R from Braskem, VA content of 14%, bio-based content of 60%), 8 parts of POE (DuPont 8100, MFR=1.0g / 10min), 10 parts of TPU (AH-560 from BASF, softening temperature of 85.0-105°C), 48 parts of lignin-GMA-EVA composite material, and 3.07 parts of AC foaming agent, 0.03 parts of DCP, 2 parts of zinc oxide, 0.3 parts of calcium stearate and 0.6 parts of erucamide are used. After being mixed evenly in proportion, they are added to a twin-screw extruder. The temperature of the extruder is set to 80°C-100°C-130°C-140°C-140°C-140°C-140°C-140°C-140°C-140°C-135°C at the die head, the feeding speed is 15rpm, the main engine speed is 145rpm, and the bio-based foaming modified material is obtained by heating and extrusion.

[0087] Example 7

[0088] According to the weight fraction ratio, 75 parts of lignin (500 mesh) were added with 1.5 parts of titanate coupling agent, and stirred in a reactor at 50±5°C for 1 hour; then 0.04 parts of potassium persulfate, 0.015 parts of N,N-methylenebisacrylamide, and 23.445 parts of EVA-g-GMA (Sumitomo BF-2B, GMA monomer content 12%, melt flow rate MFR = 3g / 10min) were added, and the mixture was stirred and mixed evenly, and then released for use.

[0089] The above blended materials were added into the feeding hopper of a twin-screw extruder, and the temperature of the twin-screw extruder was set to: 80°C-100°C-130°C-140°C-140°C-140°C-140°C-140°C-140°C-140°C-135°C (die head), feeding speed of 15 rpm, and main engine speed of 145 rpm to prepare lignin-GMA-EVA composite material.

[0090] By weight, 25 parts of EVA (SVT2145R from Braskem, VA content 30%, bio-based content 40%), 8 parts of POE (DuPont 8100, MFR = 1.0g / 10min), 10 parts of TPU (AH-560 from BASF, softening temperature 85.0-105°C), 50 parts of lignin-GMA-EVA composite material, and 4.46 parts of AC foaming agent, 0.04 Parts of DCP, 1.5 parts of zinc oxide, 0.2 parts of calcium stearate and 0.8 parts of erucamide were mixed uniformly in proportion and added into a twin-screw extruder. The temperature of the extruder was set to 80℃-100℃-130℃-140℃-140℃-140℃-140℃-140℃-140℃-140℃-135℃ for the die head, the feeding speed was 15rpm, the main engine speed was 145rpm, and the bio-based foaming modified material was obtained by heating and extrusion.

[0091] The performance of the modified material with high bio-based content prepared in Examples 4 to 7 was compared with that of the traditional EVA material midsole. The test results are shown in Table 1 below.

[0092] Table 1. Performance comparison table.

[0093]

[0094] From the above results, it can be seen that the material prepared in the embodiment of the present invention has a similar density, slightly higher tensile strength and elongation at break, and similar or slightly higher other properties than traditional EVA midsole foaming, and can meet the midsole foaming performance requirements. Compared with traditional EVA materials, the bio-based content in the material obtained in the embodiment of the present invention is higher.

[0095] The modified material with high bio-based content and the preparation method thereof provided by the present invention are realized by a two-step method, wherein the first step is to prepare a lignin composite material, and the surface of the lignin is modified to become a hydrophobic material; and the second step is to prepare a bio-based composite material. The lignin used is a natural biomass material and has good environmental protection. The prepared biomass foaming material has the advantages of being renewable and environmentally friendly.

[0096] Since lignin is a hydrophilic material, the surface needs to be modified with a phthalate coupling agent to make the surface hydrophobic. Then, EVA-g-GMA is added to graft GMA groups on the lignin surface to better react with other polymer materials. This requires the addition of an initiator and a first crosslinking agent as auxiliary modifications. EVA is a bio-based material prepared from sugarcane. It has the function of renewable raw materials and is the core substrate in foaming materials. The purpose of adding POE is to play a role in rebound and anti-slip in the blended material system. The addition of TPU can keep the performance of the blended material system stable. The foaming agent uses AC foaming agent, which is the main chemical foaming agent in the field of EVA-based foaming. The second crosslinking agent mainly uses one of BIPB or DCP, which is also the main crosslinking agent in the field of EVA-based foaming. At the same time, it is supplemented with zinc oxide and calcium stearate to play a role in dispersion and internal lubrication. In order to have good surface demoulding properties of the product during the molding process, some erucamide is added.

[0097] The present invention utilizes the characteristics of plant cellulose as a natural material, which is renewable, degradable, low-priced and of good quality, and solves the problem of poor interface compatibility between the polymer matrix and the plant fiber. The obtained modified material with a high bio-based content can replace non-degradable materials, reduce pollution, and achieve true environmental protection and natural degradation.

[0098] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.

Claims

1. A method for preparing a modified material with a high bio-based content, characterized in that: The method comprises: Step 1, weigh each raw material according to proportion; Step 2, preparing a lignin composite material: modifying the surface of lignin to obtain a lignin hydrophobic material, and then preparing a lignin-GMA-EVA composite material; Step 3, preparing a bio-based composite material: uniformly mixing the lignin-GMA-EVA composite material obtained in step 2 with EVA, POE, TPU, a foaming agent, a cross-linking agent, zinc oxide, calcium stearate and erucamide, and extruding the mixture by heating to prepare a bio-based foaming modified material.

2. The method for preparing a modified material with a high bio-based content according to claim 1, characterized in that: In the step 2, a titanate coupling agent is first added to the lignin, and the mixture is heated and stirred in a reaction kettle to modify the surface of the lignin into a hydrophobic material, and then the lignin is taken out for standby use. The obtained lignin hydrophobic material is then mixed and extruded with EVA-g-GMA through the action of an initiator and a first cross-linking agent to prepare a hydrophobic lignin-GMA-EVA composite material.

3. The method for preparing a modified material with a high bio-based content according to claim 2, characterized in that: In the step 2, by mass percentage, the amount of titanate coupling agent is 0.5%-1.5% of the total mass, the amount of initiator is 0.02%-0.04% of the total mass, the amount of the first cross-linking agent is 0.01%-0.015% of the total mass, the amount of EVA-g-GMA is 18%-25% of the total mass, and the balance is lignin.

4. The method for preparing a modified material with a high bio-based content according to claim 3, characterized in that: In the step 2, the lignin is powder with a particle size range of 200-500 mesh; the initiator is any one of sodium persulfate or potassium persulfate; and the first cross-linking agent is N,N-methylenebisacrylamide.

5. The method for preparing a modified material with a high bio-based content according to claim 4, characterized in that: In the step 2, firstly, a titanate coupling agent is added to the lignin, and then the mixture is put into a reactor together, stirred for 1 hour at a temperature of 50±5°C, and then taken out, and then the lignin treated with the titanate coupling agent and the initiator, the first cross-linking agent, and the EVA-g-GMA are mixed in proportion, and added to a twin-screw extruder, and the extruder temperature is set to 80°C-100°C-130°C-140°C-140°C-140°C-140°C-140°C-140°C-140°C-135°C for the die head, the feeding speed is 15rpm, the main engine speed is 145rpm, and the lignin-GMA-EVA composite material is obtained by heating and extrusion.

6. The method for preparing a modified material with a high bio-based content according to claim 1, characterized in that: In the step 3, EVA, POE, TPU, lignin-GMA-EVA composite material, foaming agent, second cross-linking agent, zinc oxide, calcium stearate and erucic acid amide are mixed uniformly in proportion and added to a twin-screw extruder, and the extruder temperature is set to 80°C-100°C-130°C-140°C-140°C-140°C-140°C-140°C-140°C-140°C-135°C for the die head, the feeding speed is 15rpm, the main engine speed is 145rpm, and the bio-based foaming modified material is obtained by heating and extrusion.

7. The method for preparing a modified material with a high bio-based content according to claim 6, characterized in that: In the step 3, by mass percentage, the amount of lignin-GMA-EVA composite material is 45-50% of the total mass of the mixture; the amount of foaming agent is 3-5% of the total mass of the mixture; the amount of the second cross-linking agent is 0.03-0.05% of the total mass of the mixture; the amount of zinc oxide is 1.5-2% of the total mass of the mixture; the amount of calcium stearate is 0.15-0.3% of the total mass of the mixture; and the amount of erucamide is 0.5-0.8% of the total mass of the mixture.

8. The method for preparing a modified material with a high bio-based content according to claim 7, characterized in that: In the step 3, the foaming agent is AC foaming agent; the second cross-linking agent is any one of BIPB and DCP.

9. The method for preparing a modified material with a high bio-based content according to claim 6, characterized in that: In the step 3, by mass percentage, EVA uses a material with a VA content of 14-30% and a bio-based content of 40-70%, and the amount of EVA is 25-30% of the total mass of the mixture; POE uses a material with a melt index of 1g / 10min, and the amount of POE is 5-8% of the total mass of the mixture; TPU uses a polyester material with a melting point in the range of 100-110°C, and the amount of TPU is 8-10% of the total mass of the mixture.

10. A modified material with high biobased content prepared by the method according to any one of claims 1 to 9.